The Dilemmas of the Contemporary World - Mikolas, Zdenek (Bina Nusantara University, 2016)
The research focused on the dilemmas of the power of market society. In here, the research aimed to find the context of trends in the contemporary world and explore the main elements of society. The main elements of society were economic, political and violent forces. The main methodological principles of the research are the diagnostic â therapeutic approach to the world and the development, and the techniques of mathematical logic modeling through the description and scenarios.